Enhancement of plant growth regulators production from microalgae cultivated in treated sewage wastewater (TSW) - Walaa M. Elakbawy; Sanaa M. M. Shanab; Emad A. Shalaby (BMC Plant Biology, 2022)
Abstract The aim of this work is to develop an efficient method for detection and evaluation of the plant growth regulators produced from cyanobacteria species (Anabaena oryzae and Nostoc muscorum) cultivated on BG110, and Chlorophyta alga (Chlorella vulgaris) cultivated on BG11 in addition to the cultivation of these strains on treated sewage wastewater (TSW) combined with control media (BG11 and BG110) at different concentrations (100, 75 and 50%). Bioassays were performed on Wheat coleoptile length and Cucumber cotyledons fresh weight for indole acetic acid (IAA) and Benzyl adenine (BA) detection. In addition, application experiments of IAA and BA presence in algal extract were applied on tomato plantlets and soybean callus. The obtained results of A. oryzae and N. muscorum extracts (grown on BG110 and 100% sewage media) with optimum conc. of IAA and BA showed moderate shoot length and leaves number as well as high root initiation of tomato explant compared to control. While dimethyl sulfoxide (DMSO), IAA conc. as well as IAA + BA conc. showed no effect on branching and leaf expansion. The results of C. vulgaris (grown on BG11) also revealed that the shoot had high leaves number and greatest root initiation, without branching and leaf expansion. On the other hand, 100% TSW had a moderate shoot, leaves number and high root initiation. Extracts of A. oryzae and N. muscorum (grown on BG110) induced 1.5-fold increase in soybean callus fresh weight, while the growth on 100% TSW was shown to be less effective. Moreover, extract of C. vulgaris (grown on BG11) induced a moderate effect, while its growth on 100% TSW was shown to be less effective in soybean callus fresh weight increment.